Prevention and treatment of Clostridium difficile associated diarrhea by reconstitution of the microbiota - Noa Eliakim -Raz; Jihad Bishara (Taylor & Francis Group, 2019)
This review summarizes the latest advances in treating and preventing Clostridium difficile infection (CDI), the most common infectious disease cause of nosocomial diarrhea in adults in developed countries. As customary antibiotic therapies against C. difficile, metronidazole and vancomycin, are broad spectrum, they affect greatly the gut microbiota, which result in very high recurrence rates. Therefore, new strategies are researched intensively. New therapies focus on limiting further destruction of the gut microbiota or restoring the microbiota to its pre-destructed state. These include new antibiotics, such as fidaxomicin, which demonstrates reduced CDI recurrences, among other new drugs, biotherapeutic strategies, mainly fecal microbiota transplantation but also competitive inhibition with non-toxigenic strains of C. difficile, and finally, monoclonal antibodies against C. difficile toxins which offer protection against recurrences.